Association Between Preoperative Cognitive Performance and Postoperative Delirium in Older Patients: Results From a Multicenter, Prospective Cohort Study, and a Mendelian Randomization Study - Rao Sun; Shiyong Li; Changming Yang; Guiming Huang; Chunrong Tang; Wei Li; Zhongyuan Xia; Mingzhang Zuo; Ning Yang; Huiyu Luo; Kun Zhang; Huajun Li; et al. (MedComm)
ABSTRACT This study evaluated the association between preoperative cognitive performance and postoperative delirium (POD) using a multicenter prospective cohort, and explored potential causality using Mendelian randomization (MR) analysis. We analyzed data from 2257 patients aged ≥ 75 years undergoing elective noncardiac and noncranial surgeries across 16 Chinese medical centers. Preoperative cognitive assessment using Mini‐Cog revealed 28.4% of patients had cognitive impairment (score ≤ 2). POD occurred in 9.7% of patients, with higher incidence among those with cognitive impairment. Logistic regression demonstrated that cognitive impairment was significantly associated with increased POD risk (odds ratio [OR], 2.06; 95% confidence interval [CI], 1.55–2.74; p < 0.001). This association persisted after adjustment for demographic, preoperative, and intraoperative factors, and was confirmed through propensity score matching and inverse probability treatment weighting analyses. A nearly linear inverse association was observed between Mini‐Cog scores and POD incidence. Complementary MR analysis using 139 SNPs from European ancestry data suggested that higher cognitive performance might be associated with decreased delirium risk (inverse‐variance weighted OR, 0.74; 95% CI, 0.59–0.93; p = 0.009). Although these results point to a potential link between preoperative cognition and POD, interpretation of causality should be approached with caution, particularly given differences in populations and genetic datasets.